Sexual practice and belief system among menopausal women in Ibadan: implication for sexual health (2009)
This is a correlation cross-sectional study aimed at investigating the sexual beliefs and practices of menopausal women in Ibadan, Oyo State, Nigeria. A systematic random sampling of women within the menopausal age was used to select the respondents; 101 women were selected from schools, churches, civil service and markets. A self-constructed questionnaire was used to collect data. Focussed group discussion was also used. The ages of the women ranged between 41 and 65, with the mean age of 47. The results indicated that the three independent variables were potent predictors and accounted for 26.1% variance of sexual practices o f menopausal women. However, only sexual beliefs had significant contribution to the criterion measure. Some women claimed that they had never enjoyed sex and they do not want to continue in the act; some were afraid, believing that sexual intercourse during this period could result in ill health. It was recommended that sexuality health education should be used to tackle the problem of ignorance in this respect, as it could lead to conflict in the family.